Dinamika Psikologis Pelaku Kekerasan Seksual pada Anak - Kayla, Baiq Ghassani; Ali Ramzi; Febbi Anggy; Herodya L Fesmia; Pujiarrohman (Lombok Medical Journal, 2023)
Nowadays cases of sexual violence against children are rife in Indonesia. Cases of sexual violence increase over time. The perpetrators of sexual violence are not only strangers who are not known to the victim, but also the closest people to the victim, such as fathers, uncles, or grandfathers. Ironically, perpetrators of sexual violence in children today are not only carried out by adults, but also carried out by children. The types of perpetrators of sexual violence have also varied greatly, such as perpetrators of rape to perpetrators of internet sexual violence who distribute pornographic content. There are several psychological factors that underlie the perpetrators of sexual violence, such as lack of parental attention, lack of education about intimate organs, to easy access to pornographic photos or films on the internet. There are two factors that cause a person to become a perpetrator of sexual violence, first is historical factors, such as a history of past trauma and second is psychological factors, such as lack of interpersonal communication. Perpetrators of sexual violence in children must get a treatment to overcome the problems experienced. This handling must be carried out by all groups, both from the family, community, and government. Therefore, this article will discuss the psychological dynamics of perpetrators of sexual violence in children, which includes the types of perpetrators of sexual violence, the pathophysiology of psychological dynamics of perpetrators, and efforts to handle perpetrators of sexual violence.